Investigate How Rising Temperatures Affect Milk Production in Dairy Cattle and the Physiological Mechanisms Involved - Ahmad, Mukhtar; Muhammad Jamil; Saeed Ullah; Shakirullah; Ali, Mubarik (Indus Journal of Bioscience Research, 2024)
Background: Rising temperatures globally make it harder to produce dairy products, especially because heat stress influences cattle’s physiology, milk production, and reproduction. To come up with ways to keep dairy farming going in warm areas, it’s important to understand how heat stress works. Aims: The study was conducted to look into how heat stress affects the dairy cattle in Dera Ismail Khan, Pakistan, including their milk production, food intake, behavior, and ability to reproduce. Methods: From July 2023 to June 2024, 200 dairy animals (100 cows and 100 buffaloes) were used in a cross-sectional study. Physiological factors were observed, such as the temperature of the rectal area, the rate of breathing, and heart rate. The amount of milk produced and its make-up (fat, protein, and solids) were studied, along with the animals’ dry matter intake, water intake, and behavior. It was kept track of reproductive success indicators like the rate of conception and time between calves. Pearson’s association were used to look at the data. Results: Buffaloes’ rectal temperatures (39.5 ± 0.6°C) and breathing rates (45 ± 5 breaths/min) were higher than cows’ (39.2 ± 0.5°C and 42 ± 4 breaths/min). But buffaloes had higher fat (6.5 ± 0.6%) and protein (4.5 ± 0.4%), even though cows gave more milk (12.1 ± 2.3 L/day) but their fat content was significantly low. When animals were under heat stress, they ate less food and drank more water. There were strong links (p < 0.01) between the temperature-humidity index (THI) and physiological stress and a weak link (r = -0.68, p < 0.01) between THI and milk output. Reproductive performance went down, with longer times between calves and shorter periods of estrus. Conclusion: Heat stress is harmful for dairy cows because it changes their physiological stability, output and fertility. To make the animals more resilient and productive in hot places, we need to use tactics like genetic selection, better housing and changes to their nutrition.